Immune challenge affects risk sensitivity and locomotion in mosquitofish (Gambusia holbrooki) - Stella A. Encel; Ashley J. W. Ward (Royal Society Open Science)
The immune system is crucial in responding to disease-causing pathogens. However, immune responses may also cause stereotypical changes in behaviour known as sickness behaviours, which often include reduced activity. Sickness behaviours are thought to have an important role in conserving energy required to support the immune response; however, little is known about how they manifest over time or in relation to risk, particularly in fishes. Here, we induced an immune response in mosquitofish (Gambusia holbrooki) by inoculating them with Escherichia coli lipopolysaccharide (LPS). We subsequently tested batches of fish at 24 h intervals and examined: locomotory behaviour, tendency to use a refuge and fast-start response immediately following a threat stimulus (measured as peak acceleration). Control and LPS-treated fish behaved similarly on days 1, 3 and 4. However, 2 days post-inoculation, LPS fish swam more slowly and spent more time in the refuge than control fish, although no difference in post-threat peak acceleration was found. Our findings suggest that sickness behaviours peak roughly 2 days following exposure to LPS and are relatively short-lived. Specifically, immune-challenged individuals exhibit reduced locomotion and exploratory behaviour, becoming more risk averse overall while still retaining the ability to respond acutely to a threat stimulus.